Rancang Bangun Aplikasi Administrasi Rawat Jalan pada Klinik Berbasis Dekstop - Resti Lia Andharsaputri; Nurul Afni; Minda Septiani (Jurnal Sistem Informasi, 2019)
Abstract—Services in the health sector at a clinic must be done quickly, swiftly, agile, and give the best. The best service is not only seen in terms of the performance of its human resources, but also in terms of the use of technology. Utilizing increasingly developing technology will facilitate human performance in general and clinic employees in particular to obtain, manage and store data and information needed. Administration of outpatient services at the Islamic Medical Service clinic uses a system that is still manual, for example in the case of recording patient data, registration, doctor's examination, payment, taking drugs until making reports. This allows the occurrence of obstacles or human error during operations such as long queues, waiting too long, recording data that takes a long time, delay in delivery of information to reports that are not accurate in its manufacture. The purpose of this study is to make an application for desktop-based outpatient administration that can facilitate the operation of outpatient administration at this STI clinic. In making this application, the system development method used is Waterfall, the application program uses the Delphi 7 programming language and Microsoft Access 2007 as its database. The results of this study are an outpatient administration application program that can assist clinic staff in operating outpatient services ranging from registration, inspection, payment to report making so as to improve employee performance to be more effective and efficient.